Interview of Stephen O. Wilson by Brian Shoemaker - Wilson, Stephen O. (Byrd Polar Research Center Archival Program, 2005)
Captain David Nutt, pp. 2-3 Dr. Lincoln Washburn, pp. 2, 67, 71-72 Pete Scholander, pp. 3 John Coachman, pp. 3 Rear Admiral Richard E. Byrd, pp.3, 16-17, 20-21, 32, 45 Paul Siple, pp. 3, 14, 39 Eddie Goodale, pp. 3 Ken Maulton, pp. 3 Lieutenant JG Jack Tuck, pp. 4 Dave Baker, pp. 4 Gordon Ebie, pp. 6 Commander Bill Shockley pp. 8 Lee Barden, pp. 8 Charles W. Thomas, pp. 13, 41-42 Commander ________ Whitney, pp. 14 ______ Young, pp. 14 ______ Williams, pp. 14-15 Rear Admiral George Dufek, pp. 16, 20-21, 23, 36, 38, 42, 46 Captain Pat Mayor, pp. 22, 34, 66 Captain Cadwalder, pp. 22-23 Willis Tressler, pp. 26 Hardwick P. Shipley, pp. 33 P.Y. Matthews, pp. 33-34, 47 Bernard Lauff, pp. 34-35, 47 Commander Hank Jorda, pp. 36 Lieutenant Commander Donovan, pp. 36 Lieutenant Carry, pp. 36-37 Lieutenant McCaulson, pp. 37 Gus Cordiner, pp. 37 Captain Ketchum, pp. 38, 41, 66 Sir Edmund Hillary, pp. 41, 79 Harry Ayers, pp. 41 ______ Muldrew, pp. 41 Dick Cameron, pp. 43 Carl Eckland, pp. 43 Generalissimo Rafael Molinga, pp. 47 Dr. James A. Van Allen, pp. 49, 51, 55-58, 60-63 Larry Kagle, pp. 56 David Armbrewster, pp. 57-59 Lieutenant JG Merill, pp. 68 ______ Walters, pp. 68, 71 Bill Littlewood, pp. 72 Fred Ackroyd, pp. 79 John Lewis, pp. 79 Phil Smith, pp. 9 Norm Brevard, pp. 79 Floyd Paley, pp. 79 ______ Mecalf, pp. 83-84 ______ Eddy, pp. 83-84 Doctor Edgerton, pp. 86-87 Jim Zumberg, pp. 88 Doctor Herb Wright, pp. 88-89 Tor Kvinge, pp. 91 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Stephen_O_Wilson_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Stephen_O_Wilson_2.mp3 Audio Part 3: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Stephen_O_Wilson_3.mp3 Stephen Wilson worked on ships included in Operation Deepfreeze I, II, and III. His training at Dartmouth College gave him access to individuals interested in northern frontier studies, which was the topic of his senior thesis “Antarctica: A Problem of ...